Mouse dead end1 acts with Nanos2 and Nanos3 to regulate testicular teratoma incidence. - Atsuki Imai; Yoshihiko Hagiwara; Yuki Niimi; Toshinobu Tokumoto; Yumiko Saga; Atsushi Suzuki (PLoS ONE, 2020)
Spontaneous testicular teratomas (STTs) derived from primordial germ cells (PGCs) in the mouse embryonic testes predominantly develop in the 129 family inbred strain. Ter (spontaneous mutation) is a single nucleotide polymorphism that generates a premature stop codon of Dead end1 (Dnd1) and increases the incidence of STTs in the 129 genetic background. We previously found that DND1 interacts with NANOS2 or NANOS3 and that these complexes play a vital role in male embryonic germ cells and adult spermatogonia. However, the following are unclear: (a) whether DND1 works with NANOS2 or NANOS3 to regulate teratoma incidence, and (b) whether Ter simply causes Dnd1 loss or produces a short mutant DND1 protein. In the current study, we newly established a conventional Dnd1-knockout mouse line and found that these mice showed phenotypes similar to those of Ter mutant mice in spermatogenesis, oogenesis, and teratoma incidence, with a slight difference in spermiogenesis. In addition, we found that the amount of DND1 in Dnd1+/Ter embryos decreased to half of that in wild-type embryos, while the expression of the short mutant DND1 was not detected. We also found that double mutants for Dnd1 and Nanos2 or Nanos3 showed synergistic increase in the incidence of STTs. These data support the idea that Ter causes Dnd1 loss, leading to an increase in STT incidence, and that DND1 acts with NANOS2 and NANOS3 to regulate the development of teratoma from PGCs in the 129 genetic background. Thus, our results clarify the role of Dnd1 in the development of STTs and provide a novel insight into its pathogenic mechanism.